Fecal Calprotectin Level Reflects the Severity of Clostridium difficile Infection - Kim, Jieun; Kim, Heejung; Oh, Hyun Ju; Kim, Hyung Sun; Hwang, Youn Jee; Yong, Dongeun; Jeong, Seok Hoon; Lee, Kyungwon (Annals of laboratory medicine, 2017)
Clostridium difficile is a significant nosocomial and community-acquired pathogen, and is the leading cause of antibiotic-induced diarrhea associated with high morbidity and mortality. Given that the treatment outcome depends on the severity of C. difficile infection (CDI), we aimed to establish an efficient method of assessing severity, and focused on the stool biomarker fecal calprotectin (FC). FC directly reflects the intestinal inflammation status of a patient, and can aid in interpreting the current guidelines, which requires the integration of indirect laboratory parameters. The distinction of 80 patients with CDI versus 71 healthy controls and 30 severe infection cases versus 50 mild cases was possible using FC as a marker. The area under the receiver operating characteristic curves were 0.821 and 0.746 with a sensitivity of 75% and 70% and specificity of 79% and 80%, for severe versus mild cases, respectively. We suggest FC as a predictive marker for assessing CDI severity, which is expected to improve the clinical management of CDI.